Urinary infections and use of indwelling bladder catheter in pediatric unit - Maria Iranilda Queirós; Maria Aneuma Bastos Cipriano; Míria Conceição Lavinas Santos; Maria Vera Lúcia Moreira Leitão Cardoso (Rev Rene)
The aim of this research was to identify the etiologic agents of urinary tract infection in children submitted to indwelling bladder catheters, admitted in an Intensive Care Unit, the time of use and indication of catheter. The researched population was composed by children admitted in the Pediatric Unit of a teaching hospital, from July to December 2006. Data were collected from medical records. The sample was composed by 38 children using indwelling catheters. The main indication for catheterization was urine output monitoring. The time of using of the bladder catheter 21 (55. 3%) was of 7 to 30 days, 14 (36, 8%) < 7 days and 3 (7, 9%) > 30 days. The main etiologic agent verified was Escherichia coli(2.6%). It was found out that those children who used indwelling catheters showed significant urinary infection rate according to the literature.